The morpho/functional discrepancy in the cerebellar cortex: Looks alone are deceptive. - Rokni, Dan; Llinas, Rodolfo R.; Yarom, Yosef (Frontiers in Neuroscience, 2008)
In a recent report we demonstrated that stimulation of cerebellar mossy fibers synchronously activates Purkinje cells that are located directly above the site of stimulation. We found that the activated Purkinje cells are arranged in a radial patch on the cerebellar surface and that this organization is independent of the integrity of the inhibitory system. This arrangement of activity is counterintuitive. The anatomical structure with the extensive parallel fiber system implies that mossy fiber stimulation will activate Purkinje cells along a beam of parallel fibers. In this short review we highlight this discrepancy between anatomical structure and functional dynamics and suggest a plausible underlying mechanism.